Useful myths and intractable truths: the politics of the links between forests and water in Central America - Kaimowitz, D. (Cambridge University Press, 2004)
This chapter examines the policy debate related to the links between forests and water in Central America and the approaches that policymakers and others have used to address the perceived problems, with emphasis on the siltation of large reservoirs. It shows how political, institutional, and technical factors have interacted to produce positive but sub-optimal results and offers suggestions for future initiatives. While the focus is on Central America, many of the arguments presented apply to other tropical regions. The next section provides a brief history of the debates surrounding catchment issues in Central America, followed by a summary of recent scientific literature on the physical and economic links between forests, climate, and water and sediment flows. Case histories of the El Cajon hydroelectric dam in Honduras, the Lempa River basin in El Salvador, the Panama Canal, and Hurricane Mitch, are then presented. These cases have many dimensions but this paper concentrates exclusively on the aspects related to off-farm hydrological effects; there is no attempt to evaluate the projects involved, which may well be justified on the grounds. In addition, the main focus is on forest cover.